Dynamic Response Analyses of Plastic Greenhouse Structure considering Fluctuating Wind Load. (15th January 2021) - Jiang, Yingchun; Bai, Yikui; Wang, Cong; Wang, Yonggang; Pang, Xinfu
Abstract : Wind load is one of the main factors of plastic greenhouse collapse. To solve the dynamic response problem of greenhouses under wind load and determine the dangerous section of a skeleton structure, the investigated lump method is presented for the dynamic response analysis of a plastic greenhouse, considering pulsating wind on the basis of Timoshenko beam theory. First, the investigated lump is designed according to the Timoshenko beam microbody concept. On the basis of Timoshenko beam theory, the governing equations of the skeleton structure of the greenhouse are derived, and the realization process of the algorithm is also provided. Second, the accuracy and effectiveness of the proposed numerical method are verified by an example in which the bending wave of a variable cross section beam with free ends propagates. Finally, the dynamic response of the steel skeletons of plastic greenhouses is analyzed under the effect of the simulation wind speed, and the spatial distribution of the maximum node displacement and the section maximum stress of the steel skeleton are obtained. Computational results show that the displacement peak is near the top of the plastic greenhouse. The most dangerous section of the top chord in the steel skeleton is near the leeward bottom, which has a maximum stress of 219.4 MPa, and the most dangerous section of the bottom chord is near the 1 m height on the leeward side of the plastic greenhouse, which has a maximum stress of 248.5 MPa. Bending stress is the main factor of the rapid increase of stress at the bottom of the skeleton. The maximum node displacement and cross-sectional stress caused by fluctuating wind loads are higher than those caused by average wind loads. The fluctuating wind load should be considered in the wind-induced response analyses of plastic greenhouses.